Drivers of and barriers to adaptive reuse of colonial buildings in Malaysia - Athika Norlaili Abdul Halim; Mohd Aliff Izuan Md Yasin; Nor Syahila Ab Rashid; Noor Hayati Ismail (Penerbit Universiti Kebangsaan Malaysia, 2024)
Adaptive reuse of buildings is popular among developed countries when historically significant buildings are being restored in order to preserve their historical significance and use them for a greater cause. On the other hand, adaptive reuse building has not yet gained popularity in developing countries due to a lack of proper research. As the number of historic structures has been dropping daily, people's awareness has started to increase. As the first research problem arises, there is a lack of research regarding adaptive reuse, which is another way of preserving those historical buildings by revitalizing or converting them into a commercial centre for the public, and a lack of research on recommendations for solving the barriers to adaptive reuse on colonial buildings. Hence, the aims of this research are to find the best formulas for converting colonial buildings for suitable uses. Consequently, this research was required to identify the drivers and barriers associated with the adaptive reuse of colonial buildings. A comprehensive literature review was conducted to explore the concept of adaptive reuse, its aspects, drivers, and barriers, and new uses for colonial buildings. While existing literature on developed countries cannot be directly applied to Malaysia, this study fills a gap in understanding adaptive reuse in developing nations. Based on the objectives of the study, this research is expected to identify the drivers and barriers to the adaptive reuse process of colonial buildings. This exploration will come out with recommendations that could be implemented to remove or reduce the impact of the barriers identified. The findings of this research are expected to result in actionable recommendations for mitigating the identified barriers. Hence, the significance of the adaptive reuse process influences the characteristics and not only the benefits but also the potential of the process, which are classified as social, environmental, and economic.